Thermo-haemodynamic coupling during regional thigh heating: Insight into the importance of local thermosensitive mechanisms in blood circulation - Koch Esteves, N.; McDonald, J.; González-Alonso, J. (Experimental Physiology, 2024)
A positive relationship between local tissue temperature and perfusion exists, with isolated limb-segment hyperthermia stimulating hyperaemia in the heated region without affecting the adjacent, non-heated limb segment. However, whether partial-limb segment heating evokes a heightened tissue perfusion in the heated region without directly or reflexly affecting the non-heated tissues of the same limb segment remains unknown. This study investigated, in 11 healthy young adults, the lower limb temperature and haemodynamic responses to three levels of 1 h upper-leg heating, none of which alter core temperature: (1) whole-thigh (WTH; water-perfused garment), (2) quadriceps (QH; water-perfused garment) and (3) partial-quadriceps (PQH; pulsed shortwave diathermy) heating. It was hypothesised that perfusion would only increase in the heated regions. WTH, QH and PQH increased local heated tissue temperature by 2.9 ± 0.6, 2.0 ± 0.7 and 2.9 ± 1.3°C (P < 0.0001), respectively, whilst remaining unchanged in the non-heated hamstrings and quadriceps tissues during QH and PQH. WTH induced a two-fold increase in common femoral artery blood flow (P < 0.0001) whereas QH and PQH evoked a similar ~1.4-fold elevation (P = 0.0018). During QH and PQH, however, tissue oxygen saturation and laser-Doppler skin blood flow in the adjacent non-heated hamstrings or quadriceps tissues remained stable (P > 0.5000). These findings in healthy young humans demonstrate a tight thermo-haemodynamic coupling during regional thigh heating, providing further evidence of the importance of local heat-activated mechanisms on the control of blood circulation.